Emotional Intelligence and Academic Success in Higher Education: Insights from an Algerian Case Study at Mohamed Boudief University, M’Sila (El-Wahat Journal for Research and Studies, 2026)
This study examines the relationship between emotional intelligence (EI) and academic success among undergraduate students at Mohamed Boudief University, M’Sila, Algeria. Using the Emotional Intelligence Scale and GPA records from 210 participants, Pearson’s correlation revealed a moderate positive link between EI and academic achievement (r = 0.52, p < 0.01). Multiple regression showed self-motivation and emotional management as the strongest predictors of GPA. Semi-structured interviews highlighted EI’s role in stress regulation, relationship building, and goal persistence. No significant differences were found in overall EI across gender or field of study, although females scored higher in empathy and interpersonal skills. Findings suggest that EI contributes to academic performance beyond cognitive ability. Integrating EI-focused workshops and mentoring into university programs could strengthen students’ resilience, collaboration, and academic outcomes.
Keywords: emotional intelligence, university, academic success, students’ resilience, self-motivation